Experiences, perceptions and unexpressed needs of patients undergoing heart and lung transplantation in intensive care unit: a qualitative phenomenological study - Ugenti, Nikita Valentina; Quirini, Silvio; Aleandri, Marianna; Di Filippo, Vittorio; Durante, Stefano; Ferretti, Alice; Guerrieri, Carolina; Martella, Carmela; Peghetti, Angela; Sgarzi, Silvia; Valentini, Sara; Vetromile, Angela; et al. (Frontiers in Psychology, 2025)
IntroductionPatients in intensive care units require advanced clinical care as well as attention to psychological social and emotional needs, often overlooked. Heart and lung transplant recipients experience a particularly complex postoperative journey, marked by physical fragility, emotional vulnerability, and identity transformation. Communication barriers caused by sedation, intubation, and disorientation, combined with a focus on physiological stability, hinder understanding of their lived experience. A lack of qualitative research in this topic limits the development of person-centered care and mismatches between professional priorities and patient needs may lead to depersonalization and dissatisfaction. This study aimed to explore ICU experiences of transplant patients through the richness and complexity of their individual journey.MethodsA descriptive phenomenological study was conducted at IRCCS University Hospital of Bologna. Semi-structured interviews were performed with 21 heart (average ICU stay: 6 days) and lung (average ICU stay: 13 days) transplant recipients, 2–4 days post-ICU discharge. Interviews aimed to capture patients’ recollections while ensuring clinical stability. Thematic content analysis was used to identify key themes.ResultsSix main themes emerged: (1) care environment, (2) sensory perceptions, (3) person’s empowerment, (4) lived experiences, (5) transplant path, and (6) quality of care. Patients reported feelings of isolation, disorientation, frustration and impaired communication due to sedation and intubation. Emotional experiences ranged from fear and loneliness to hope and gratitude. Reflections on the donor revealed ambivalent emotions including guilt and appreciation. Personalized care, empathetic communication, and supportive relationships with healthcare professionals were seen as essential for emotional well-being and recovery.DiscussionHeart and lung transplantation is a deeply transformative experience. Beyond clinical care, patients need emotional and psychological support. Personalized, empathetic interventions and improved communication strategies are crucial to enhancing both recovery outcomes and the overall ICU experience.Clinical trial registrationClinicalTrials.gov, identifier NCT06773052.